Tool study of waves energy converter with heaving constant of 3675 N/m - Imam Fauzie; Wiwit Suprihatingsih; Abdul Hamid (JTTM : Jurnal Terapan Teknik Mesin, 2025)
As technology develops, the need for renewable energy is increasing. Ocean wave energy is one type of renewable energy and has high potential due to its abundant availability and unlimited potential range. A wave energy converter is a system that can capture wave energy and convert it into electrical energy. A simple form of periodic motion is an object vibrating at the end of a spring. Therefore it is called simple harmonic motion. The purpose of this study is to verify the performance of the wave energy converter (WEC) pontoon lift vibration based on the principle of forced undamped vibration using the spring constant value to produce optimal electrical energy. This research was conducted by experimental tests on land and on the coast of Tanjung Pasir, Tangerang. The heaving method was used to realize the use of springs in the wave energy converter (WEC). Heaving is the vertical up-and-down motion of a floating structure on undulating water. The lifting motion of a floating structure is the vibration that causes a backward force when the structure is moved from its balanced position. The results of data analysis of the identification of the smallest ocean potential energy without planets using planetary energy reached 0.095 watts, the maximum was 0.986 watts, the smallest reached 121 watts, and the largest reached 955 watts. The resulting speed value is 71.57 rpm and the maximum result is 85.12 rpm. Based on these data, we can produce larger data, which is 955 watts